Social Media as Mobile Learning Oral Chat-Based Constructive Communication to Improve Speaking Skills - Maulina; Titin Rahmiatin Rahim; Angelica Ordanza Cortez; Sheryl Ann V. Narciso; Anwar Said (Decode: Jurnal Pendidikan Teknologi Informasi, 2023)
WhatsApp is one of the most practical, cost-effective, and communicative mobile applications for college students to enhance their speaking skills. This study reconciled to consuetude college students to flexible habitual use of the English language learning and intended to improve their speaking abilities with specially tailored learning resources and activities aid known as WhatsApp-based speaking instructional material (WABSIM). This exploratory mixed-methods research evaluated oral chat-based utilization of WhatsApp by twenty-eight students for one semester using audio voice messages and video recordings of communicative activities in pairs or groups, dialogues, and interviews activities recorded in the WhatsApp group managed to produce every day classroom and noncollegiate activities. Speaking test consisted of an oral evaluation of student's fluency, vocabulary used, grammar, pronunciation, and comprehensibility aspects. It reveals that students demonstrated a stupendous developing speaking interest in building English sentences by raising questions and delivering responses, improved learning collaboration, created better learning engagement, increased learning self-awareness, and accelerated flexible communication. Besides, students achieved substantial academic progress astoundingly in a semester. Therefore, to emerge the significance acknowledged from this current study, in the current era of mobile technology advancement supporting teaching and learning English, WhatsApp oral chat-based assistance offering teaching and learning English flexibility is the most effective.